Expedient synthesis of 1,2,3-triazole-fused tetracyclic compounds by intramolecular Huisgen ('click') reactions on carbohydrate-derived azido-alkynes - Hotha, Srinivas; Anegundi, Ramakrishna I.; Natu, A. A. (Tetrahedron Letters, 2005)
An efficient, practical and convenient synthesis of 1,2,3-triazole-fused tetracyclic compounds was achieved by intramolecular 1,3-dipolar cycloaddition of carbohydrate-derived azido-alkynes. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Click chemistry; Cycloaddition; diversity oriented synthesis; Huisgen reaction